(untitled) (Indianapolis, 1994)
The ultimate resource guide for beginning to intermediate users of Microsoft Project for Windows-the leading project management software!Covers the basics of project management, using views, reports, and several advanced topicsFeatures finished, polished examples, a table of shortcuts, a helpful glossary of terms, and much moreShows readers how to manage a project with tools provided in the Project Manager
Keywords: Project management,Microsoft Project,Quản trị dự án,Quản trị dự án; Computer programs,Chương trình máy tính